Quantitative analysis of water quality parameters and their influence on the Pacific white shrimp (Litopenaeus vannamei) culture: A case study of Rancong mariculture area in Lhokseumawe, Aceh, Indonesia - Yessy, Lailan Try; Ezraneti, Riri; Khalil, Munawar (Universitas Malikussaleh, 2024)
Water quality is one of several aspects that affect the success of aquaculture business. This study analyzes water quality and assesses its impact on aquaculture enterprises in the Rancong pond region of Lhokseumawe City. The study ran from November to December 2018. The water quality of the Rancong pond was sampled directly and tested in multiple labs. The field survey and purposive sampling strategy separated the research location into four stations with three water sampling points. Temperature, salinity, turbidity, brightness, pH, dissolved oxygen, alkalinity, total organic matter, BOD5, total ammonia nitrogen, nitrite, nitrate, phosphate, lead (Pb), total Vibrio bacteria, total general bacteria, and phytoplankton types and abundance were measured. The suitability of water quality is assessed using descriptive analysis, scoring, and matching. The investigation indicates that the quality and maintenance of the source water are highly suitable (S1). Traditional vannamei shrimp ponds in Rancong, Lhokseumawe City, should be maintained as fisheries cultivation areas.